cis–trans-Amide isomerism of the 3,4-dehydroproline residue, the ‘unpuckered’ proline - Kubyshkin, Vladimir; Budisa, Nediljko (Beilstein Journal of Organic Chemistry, 2016)
Proline (Pro) is an outstanding amino acid in various biochemical and physicochemical perspectives, especially when considering the cis–trans isomerism of the peptidyl-Pro amide bond. Elucidation of the roles of Pro in chemical or biological systems and engineering of its features can be addressed with various Pro analogues. Here we report an experimental work investigating the basic physicochemical properties of two Pro analogues which possess a 3,4-double bond: 3,4-dehydroproline and 4-trifluoromethyl-3,4-dehydroproline. Both indicate a flat pyrroline ring in their crystal structures, in agreement with previous theoretical calculations. In solution, the peptide mimics exhibit an almost unchanged equilibrium of the trans/cis ratios compared to that of Pro and 4-trifluoromethylproline derivatives. Finally we demonstrate that the 3,4-double bond in the investigated structures leads to an increase of the amide rotational barriers, presumably due to an interplay with the transition state.
Keywords: amino acids; cis–trans isomerism; fluorine; pKa; proline

(untitled) - Owens, N. W.; Braun, C.; O’Neil, J. D.; Marat, K.; Schweizer, F. (J. Am. Chem. Soc., 2007)

(untitled) - Renner, C.; Alefelder, S.; Bae, J. H.; Budisa, N.; Huber, R.; Moroder, L. (Angew. Chem., Int. Ed., 2001)

(untitled) - Lu, K. P.; Finn, G.; Lee, T. H.; Nicholson, L. K. (Nat. Chem. Biol., 2007)

(untitled) - Kern, D.; Schutkowski, M.; Drakenberg, T. (J. Am. Chem. Soc., 1997)

(untitled) - Kleinpeter, E. (J. Mol. Struct., 1996)

(untitled) - Kang, Y. K.; Choi, H. Y. (Biophys. Chem., 2004)

(untitled) - Braga, C. B.; Ducati, L. C.; Tormena, C. F.; Rittner, R. (J. Phys. Chem. A, 2014)

(untitled) - Kim, W.; Hardcastle, K. I.; Conticello, V. P. (Angew. Chem., Int. Ed., 2006)

(untitled) - Thomas, C. A.; Talaty, E. R.; Bann, J. G. (Chem. Commun., 2009)

(untitled) - Eberhardt, E. S.; Panasik, N., Jr; Raines, R. T. (J. Am. Chem. Soc., 1996)

(untitled) - Hodges, J. A.; Raines, R. T. (J. Am. Chem. Soc., 2005)

(untitled) - Shoulders, M. D.; Hodges, J. A.; Raines, R. T. (J. Am. Chem. Soc., 2006)

(untitled) - Kümin, M.; Sonntag, L.-S.; Wennemers, H. (J. Am. Chem. Soc., 2007)

(untitled) - Erdmann, R. S.; Wennemers, H. (Angew. Chem., Int. Ed., 2011)

(untitled) - Siebler, C.; Erdmann, R. S.; Wennemers, H. (Angew. Chem., Int. Ed., 2014)

(untitled) - Delaney, N. G.; Madison, V. (J. Am. Chem. Soc., 1982)

(untitled) - De Poli, M.; Moretto, A.; Crisma, M.; Peggion, C.; Formaggio, F.; Kaptein, B.; Broxterman, Q. B.; Toniolo, C. (Chem. – Eur. J., 2009)

(untitled) - Torbeev, V.; Ebert, M.-O.; Dolenc, J.; Hilvert, D. (J. Am. Chem. Soc., 2015)

(untitled) - Beausoleil, E.; Lubell, W. D. (Biopolymers, 2000)

(untitled) - Lummis, S. C. R.; Beene, D. L.; Lee, L. W.; Lester, H. A.; Broadhurst, W.; Dougherty, D. A. (Nature, 2005)

(untitled) - Melis, C.; Bussi, G.; Lummis, S. C. R.; Molteni, C. (J. Phys. Chem. B, 2009)

(untitled) - Galardy, R. E.; Alger, J. R.; Liakopoulou-Kyriakides, M. (Int. J. Pept. Protein Res., 1982)

(untitled) - Shireman, B. T.; Miller, M. J.; Jonas, M.; Wiest, O. (J. Org. Chem., 2001)

(untitled) - Humbert-Voss, E.; Arrault, A.; Jamart-Grégoire, B. (Tetrahedron, 2014)

(untitled) - Duttagupta, I.; Misra, D.; Bhunya, S.; Paul, A.; Sinha, S. (J. Org. Chem., 2015)

(untitled) - Dumy, P.; Keller, M.; Ryan, D. E.; Rohwedder, B.; Wöhr, T.; Mutter, M. (J. Am. Chem. Soc., 1997)

(untitled) - Chaume, G.; Barbeau, O.; Lesot, P.; Brigaut, T. (J. Org. Chem., 2010)

(untitled) - Feytens, D.; Chaume, G.; Chassaing, G.; Lavielle, S.; Brigaut, T.; Byun, B. J.; Kang, Y. K.; Miclet, E. (J. Phys. Chem. B, 2012)

(untitled) - Flores-Ortega, A.; Casanovas, J.; Zanuy, D.; Nussinov, R.; Alemán, C. (J. Phys. Chem. B, 2007)

(untitled) - Kang, Y. K.; Park, H. S. (Pept. Sci., 2009)

(untitled) - Salvador, R. A.; Tsai, I.; Marcel, R. J.; Felix, A. M.; Kerwar, S. S. (Arch. Biochem. Biophys., 1976)

(untitled) - Kerwar, S. S.; Felix, A. M. (J. Biol. Chem., 1976)

(untitled) - Cooper, J. B.; Varner, J. E. (Plant Physiol., 1983)

(untitled) - Doerfel, L.; Wohlgemuth, I.; Kubyshkin, V.; Starosta, A. L.; Wilson, D. N.; Budisa, N.; Rodnina, M. V. (J. Am. Chem. Soc., 2015)

(untitled) - Kubyshkin, V.; Afonin, S.; Kara, S.; Budisa, N.; Mykhailiuk, P. K.; Ulrich, A. S. (Org. Biomol. Chem., 2015)

(untitled) - Bedford, G. R.; Sadler, P. J. (Biochim. Biophys. Acta, 1974)

(untitled) - Evans, C. A.; Rabenstein, D. L. (J. Am. Chem. Soc., 1974)

(untitled) - Shoulders, M. D.; Raines, R. T. (Annu. Rev. Biochem., 2009)

(untitled) - Jenkins, C. L.; Lin, G.; Duo, J.; Rapolu, D.; Guzei, I. A.; Raines, R. T.; Krow, G. R. (J. Org. Chem., 2004)

(untitled) - Panasik, N. J.; Eberhardt, E. S.; Edison, A. S.; Powell, D. R.; Raines, R. T. (Int. J. Pept. Protein Res., 1994)

(untitled) - Torbeev, V. Y.; Fumi, E.; Ebert, M.-O.; Schweizer, W. B.; Hilvert, D. (Helv. Chim. Acta, 2012)

(untitled) - Kubyshkin, V. S.; Mykhailiuk, P. K.; Afonin, S.; Ulrich, A. S.; Komarov, I. V. (Org. Lett., 2012)

(untitled) - Hanessian, S.; Reinhold, U.; Gentile, G. (Angew. Chem., Int. Ed. Engl., 1997)

(untitled) - Berger, G.; Vilchis-Reyes, M.; Hanessian, S. (Angew. Chem., Int. Ed., 2015)

(untitled) - Bartlett, G. J.; Choudhary, A.; Raines, R. T.; Woolfson, D. N. (Nat. Chem. Biol., 2010)

(untitled) - Choudhary, A.; Gandla, D.; Krow, G. R.; Raines, R. T. (J. Am. Chem. Soc., 2009)

(untitled) - Fischer, S.; Dunbrack, R. L., Jr; Karplus, M. (J. Am. Chem. Soc., 1994)